PENGARUH LITERASI KEUANGAN DAN LITERASI DIGITAL TERHADAP PREFERENSI MENGGUNAKAN QRIS BSI MOBILE (STUDI KASUS GEN Z DI KOTA MALANG) - Nurdien, Faiz Ghifary; Galuh, Ajeng Kartika (Islamic Economics and finance in Focus, 2023)
Digital transformation in the financial industry creates new innovations, namely fintech, mobile banking is one of the mobile payment-based fintech products. BSI as a new bank digitizes by creating BSI Mobile which provides QRIS as a payment method whose use has increased positively. As a digital-based financial innovation technology product, financial literacy and digital literacy are needed in the provision of its use, even in the literacy of the Indonesian people both financial and digital has increased positively. So this research was conducted to examine the effect of financial literacy and digital literacy on preferences for using QRIS BSI Mobile among Gen Z in Malang City. Quantitative research type descriptive approach. With purposive sampling technique using the Lemeshow formula, 100 respondents were obtained. Data was analyzed using ordinal regression. The results showed that financial literacy and digital literacy have an influence on preferences for using QRIS BSI Mobile. The conclusion of the research results shows that the preference to use QRIS BSI Mobile among Gen Z in Malang City is influenced by financial literacy and digital literacy possessed by its users.